Purchasing : selection and procurement for the hospitality industry, Student workbook. / Andrew Hale Feinstein, John M. Stefanelli - Feinstein, Andrew Hale
The purchasing function in the hospitality industry involves ordering procedures, distribution systems, price and payment, storage and security, and specifications for food items. This book combines generally accepted purchasing principles with applications specific to the hospitality industry.